2018
DOI: 10.1111/jcmm.13494
|View full text |Cite
|
Sign up to set email alerts
|

The essential function of CARD9 in diet‐induced inflammation and metabolic disorders in mice

Abstract: Inflammation and metabolic disorder are common pathophysiological conditions, which play a vital role in the development of obesity and type 2 diabetes. The purpose of this study was to explore the effects of caspase recruitment domain (CARD) 9 in the high fat diet (HFD)‐treated mice and attempt to find a molecular therapeutic target for obesity development and treatment. Sixteen male CARD9−/− and corresponding male WT mice were fed with normal diet or high fat diet, respectively, for 12 weeks. Glucose toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…CARD9 deficiency with decreased inflammation could be a protective factor in diet‐induced obesity via inhibition of the CARD9/MAPK pathway. In deed, CARD9 KO mice display a reduction in HFD‐induced impairment of glucose tolerance and insulin resistance with decreased expressions of p38 MAPK, JnK, and ERK compared to WT mice ( 109 ). O 2 consumption, CO 2 production, and heat production are also altered in CARD9 KO mice ( 109 ).…”
Section: Card9 and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…CARD9 deficiency with decreased inflammation could be a protective factor in diet‐induced obesity via inhibition of the CARD9/MAPK pathway. In deed, CARD9 KO mice display a reduction in HFD‐induced impairment of glucose tolerance and insulin resistance with decreased expressions of p38 MAPK, JnK, and ERK compared to WT mice ( 109 ). O 2 consumption, CO 2 production, and heat production are also altered in CARD9 KO mice ( 109 ).…”
Section: Card9 and Diseasesmentioning
confidence: 99%
“…In deed, CARD9 KO mice display a reduction in HFD‐induced impairment of glucose tolerance and insulin resistance with decreased expressions of p38 MAPK, JnK, and ERK compared to WT mice ( 109 ). O 2 consumption, CO 2 production, and heat production are also altered in CARD9 KO mice ( 109 ). CARD9 could contribute to ambient PM 2.5 -induced pulmonary injury in mice through mediating Th17 cell differentiation ( 110 ).…”
Section: Card9 and Diseasesmentioning
confidence: 99%
“…A recent study conducted by Yang et al indicated that CARD9 deficiency mitigated the high fat diet (HFD)-induced metabolic disorders and inflammation by suppressing p38 MAPK and NF-κB signaling pathways [5] . In HFD-treated mice, CARD9 deficiency ameliorated adiposis, diminished the excessive lipid accumulation, and alleviated adiposity-associated symptoms including glucose tolerance impairment, inflammation and hepatopathy.…”
Section: The Promotive Role Of Card9 In Obesitymentioning
confidence: 99%
“…Yang et al revealed that CARD9 accelerated the development of IR and increased the activation of p38 and NF-κB in HFD-fed mice [5] . Besides, Cao et al found that CARD9 deficiency retarded the development of IR and decreased p38 activation [6] .…”
Section: The Promotive Role Of Card9 In Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation